Machine learning-assisted sensor array based on single trimetallic nanozyme with multienzyme-like activities for rapid and intelligent identification of multiple metal ions - Yuxuan Shen; Xincheng Xie; Chunmeng Deng; Xiaolei Geng; Yanfei Yang; Yu Luan; Yanmin Zou; Kun Zeng; Qiu Shen; Dali Wei; Zhen Zhang; Hongjun Zhao (Analytica Chimica Acta, 2026)

A novel two-layered hydroxyapatite-strengthened anammox-partial denitrification/anammox reactor for advanced nitrogen removal : Performance and mechanisms - Shenghao Ji; Hongjun Zhao; Shen Cui; Yujie Chen; Haojie Qin; Kengo Kubota; Jianyong Liu; Yu-You Li (Water Research, 2026)

When and where do university-related travelers use ride-hailing? Evidence from 75 universities in Tianjin, China - Xinwei Ma; Jichi Zhao; Weijie Yu; Hongjun Cui; Yang Liu (Journal of Transport Geography, 2026)

Mass-flow control enhances nitrogen removal in a three-stage partial nitritation, anammox and partial denitrification/anammox system treating food waste digestate: Performance and N2O release characteristics - Shenghao Ji; Shen Cui; Hongjun Zhao; Haojie Qin; Tianyi Zhang; Yu Qin; Jianyong Liu; Yu-You Li (Environmental Research, 2026)

Secondary growth enables post-healing of stress-induced cracks in 2D Zr-MOF membrane for enhanced water purification - Miaomiao Tian; Haochen Shen; Cheng Chen; Libo Zhao; Wei Yu; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Interfacial energy homogenization enables β-phase transition and high piezoactivity in MOF/PVDF membrane for sustainable pollutant degradation - Zi Yang; Miaomiao Tian; Cheng Chen; Zhiyu Zhao; Libo Zhao; Jiujing Xu; Wei Yu; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Construction of MOF-decorated 3D printed membrane with hierarchical surface functionalization for oil-water separation: Role of interfacial energy barrier - Jingtao Hu; Zhiyu Zhao; Hua Li; Saleem Raza; Ying Liu; Cheng Chen; Wei Yu; Yanchao Xu; Hongjun Lin; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2026)

Polystyrene microplastics induce auditory neurotoxicity in mammals: Integrated multi-omics profiling reveals oxidative damage and synaptic molecular dysregulation - Huanzhi Wan; Jingchun Liu; Xuan Yu; Ting Li; Wenting Yu; Bo Liu; Yingzhao Liu; Yuanyuan Zhang; Shimin Zong; Qingquan Hua; Hongjun Xiao (Journal of Hazardous Materials, 2026)

Deep Immunophenotyping Unravels the Double Negative T cells and PD-1-Mediated Inflammatory Exhaustion in Ankylosing Spondylitis - Lu Bai; Jian Gao; Yunyun Xu; Yuexin Yu; Jing Liu; Mathias Hochgerner; Hejian Zou; Xingdong Chen; Feng Qian; Hongjun He; Jiucun Wang (Phenomics, 2026)
Ankylosing spondylitis (AS) is a chronic, immune-mediated inflammatory disorder primarily affecting the axial skeleton. It is characterized by bony fusion and syndesmophyte formation of the spine, leading to compromised mobility, reduced quality of life and increased mortality. However, the underlying immune dysregulation in AS remains poorly understood. We comprehensively profiled the peripheral immune landscape of 30 patients with active AS, all of whom were TNF-α blocker-naïve, capturing the immune profile during the active disease phase without biologic interference. Using advanced 11-color flow cytometry and FlowSOM clustering, 584 immunophenotypes were analyzed in AS and 30 age-and sex-matched healthy controls, with emphasis on both cellular composition and functional characteristics. AS patients displayed a distinctive functional “activated-exhausted” immune phenotype, dominated by CD4 + CD28 + CD38 + PD-1 + T cells and HLA-DR + CD38 + CD4 − CD8 − double-negative (DN) T cells. DN T cells were significantly enriched in HLA-B27-positive patients, suggesting potential as a biomarker. Network analysis revealed seven central immune subsets associated with active disease, while functional assessment demonstrated impaired CD95 + CD8 + T cell apoptosis and disrupted B-cell maturation. These findings provide a detailed functional immune map of biologic-naïve active AS, offering novel mechanistic insights and identifying candidate biomarkers for precision intervention.

Grain tailoring enables robust high-temperature ferroelectricity in ultrathin Hf1–xZrxO2 films - Haoyu Lu; Yu Li; Liyang Ma; Geng Huangfu; Xuanyu Zhao; Changsong Xu; Hongjun Xiang; Yingfen Wei; Hao Jiang; Qi Liu; Ming Liu (Science Bulletin, 2026)

Tidal current-induced local scour around offshore tripile foundations: A CFD study of flow-structure-sediment interaction - Hongjun Liu; Wei He; Qi Yang; Lu Jing; Peng Yu; Xinyu Liu; Jieru Zhao (Ocean Engineering, 2026)

Tire wear particles induce a functional trade-off in bioretention systems: Coupled effects on nitrogen removal and greenhouse gas emissions - Gaoju Zou; Niling Zou; Yinghui Tang; Qinyi Wang; Hongjun Xiao; Quanhong Chen; Zhen Liu; Kaifeng Wang; Fan Yang; Huachao Zhao; Yu Qin; Anke Du; et al. (Environmental Research, 2026)

Soil moisture mapping using radio signal strength and gaussian process regression - Hongjun Yu; Erik Muller; Alex McBratney; Salah Sukkarieh (Precision Agriculture, 2026)
Background Soil moisture is a key variable in precision agriculture, affecting irrigation management, crop productivity, and water-use efficiency. However, field-scale soil moisture monitoring remains challenging because conventional sensing approaches are often costly and provide limited spatial coverage. This study proposes a simulation-based framework for soil moisture mapping that integrates near-ground radio-frequency (RF) sensing, Gaussian Process Regression (GPR), and adaptive sample selection Methods Received signal strength (RSS) measurements obtained from paired RF sensors were used as path-averaged proxies for soil moisture. GPR was employed to reduce measurement noise and reconstruct spatial soil moisture distributions from sparse ground-truth observations. An error-driven adaptive sampling strategy was developed to identify locations for additional soil moisture measurements under constrained sampling budgets. The framework was evaluated using numerical simulations based on synthetic soil moisture fields with varying levels of spatial variability and measurement noise. Results Simulation results demonstrated that the proposed framework reduced soil moisture estimation error compared with random sampling and conventional GPR interpolation when only a limited number of samples were available. The adaptive sampling strategy improved the efficiency of data collection by prioritizing regions with higher prediction uncertainty. Reconstruction accuracy was influenced by both soil moisture variability and measurement noise, highlighting the importance of sensor quality and field heterogeneity in system performance. Conclusion The study demonstrates the potential of combining RSS-based RF sensing, probabilistic regression, and adaptive sampling for low-cost and scalable soil moisture mapping in precision agriculture. Although the framework was evaluated only under idealized simulation conditions and no field validation was conducted, the results provide proof of concept and support future development, field testing, and extension of the approach for practical agricultural applications.

Opening the window to the solar-driven world of MXenes: Mechanisms, synergistic strategies, and emerging applications for sustainable environmental purification - Xiao Zhang; Yingzi Du; Wenzhe Yu; Mingzhu Zhou; Xiang Cai; Leihong Zhao; Hongjun Lin; Bisheng Li (Critical Reviews in Environmental Science and Technology, 2026)

Trade-off in bioretention: Tire wear particles mitigate sulfamethoxazole toxicity but exacerbate antibiotic resistance propagation - Quanhong Chen; Niling Zou; Yinghui Tang; Hongjun Xiao; Gaoju Zou; Kaifeng Wang; Jiayue Zhu; Zhen Liu; Dehua Du; Yu Qin; Anke Du; Yao Chen (Journal of Water Process Engineering, 2026)

Bidirectional seismic kinematic coupling responses of large-diameter tunnels in sloping sites under Rayleigh waves: Analytical solutions using Green’s functions - Bin Li; Jiguo Liu; Yu Miao; Hongjun He (Tunnelling and Underground Space Technology, 2026)

Health risks from PM2.5-bound heavy metals from religious burning activities on the plateau - Zhaoquan Yu; Lei Yang; Jiawei Yin; Haomiao Niu; Zhou Xu; Hao Qin; Liuyang Guo; Yan Liu; Lin Wu; Qijun Zhang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Integrating adsorptive filtration and visible-light peroxymonosulfate activation in a Fe3O4@ZIF-67@polydopamine/PTFE membrane for one-pass treating copper–tetracycline mixed wastewater - Zengjian Zhao; Tao Jian; Wenzhe Yu; Jiaheng Teng; Leihong Zhao; Qian Lei; Hongjun Lin (Chemical Engineering Journal, 2026)

From energy-limited to substrate-limited: Machine learning reveals the spatially shifting controls on cirque morphology in high Mountain Asia - Jinrong Hu; Fuyuan An; Li Yan; Hongjun Yu; Longfei Gai; Xue Min; Ruiyang Xu (CATENA, 2026)

How sea-land breezes affect ozone in coastal cities: spatial and temporal patterns - Naixiu Sun; Ya-nan Wang; Yu Fei; Lin Wu; Yicheng Yang; Liwei Li; Xueling Yang; Hongjun Mao (Environmental Monitoring and Assessment, 2026)

Evaluating the effectiveness of tightened emission standards in reducing real-world vehicle emissions: Evidence from on-road testing and inventory analysis - Lei Yang; Zhaoquan Yu; Haomiao Niu; Hao Qin; Jiawei Yin; Zhou Xu; Yan Liu; Lin Wu; Jianfei Peng; Hongjun Mao; Qijun Zhang (Journal of Cleaner Production, 2026)

Identify emission-abnormal heavy-duty diesel vehicles via on-board diagnostic urea analysis - Zeping Cao; Liuyang Guo; Zhaoquan Yu; Xiaoyang Zhao; Jiawei Yin; Zhenyu Jia; Jianlong Wang; Miao Tang; Qijun Zhang; Hongjun Mao (Journal of Environmental Sciences, 2026)

Monsoon and sea-level induced environmental shifts in the Bohai Sea, East Asia during the early-middle Pleistocene - Nanze Liang; Yibing Li; Yan Li; Haifeng Wang; Hongjun Yu; Xingyong Xu; Qiao Su; Xingyu Jiang; Guangquan Chen; Tengfei Fu; Weiwei Chen; Liang Yi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The startup characteristics of a one-stage PNA process under the Fe-free influent condition with iron-containing sludge as inoculum - Yan Guo; Qianqian Li; Hongjun Zhao; Hongzhi Ma; Xiaomin Liu; Jianguo Liu; Tianlong Zheng; Qunhui Wang; Yu-You Li (Journal of Water Process Engineering, 2026)

Dual-function tara gum-based antiscalant with efficient antiscaling and antibacterial activity: Performance and molecular simulation investigation - Liping Xiong; Wei Yu; Xinyi Lu; Zhiyu Zhao; Cheng Chen; Renjie Li; Guanhua Jin; Leihong Zhao; Hongjun Lin; Liguo Shen (Journal of Environmental Chemical Engineering, 2026)

New insights into the characteristic flavor formation of Sichuan fermented sausages driven by liquid smoke addition: An integrated study based on microbiomics, flavoromics, and untargeted metabolomics - Dong Zhang; Xinrui Xie; Changlian Yu; Yuwei Liu; Li Yang; Chang Su; Xingzhong Zhang; Hongjun Li; Jie Tang (International Journal of Food Microbiology, 2026)

Shaking table test on the seismic response of subway station in the sand-fine mixture liquefiable site - Baoguo Pei; Chuanchuan Zhang; Yimei Cheng; Yifan Xiao; Hongjun He; Xiaojian Xu; Yu Miao (Bulletin of Engineering Geology and the Environment, 2026)

Triatomic-doped MXene based catalyst with sodium alginate encapsulation their molecular and DFT calculation study for efficient photocatalytic removal of disinfected by-product from drinking water - Saleem Raza; Ata Ur Rehman; Zhiyu Zhao; Hua Li; Cheng Chen; Wei Yu; Ying Liu; Yanchao Xu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Linear diacyl chloride enables polyamide nanofiltration membranes with balanced permeability and selectivity for efficient dye desalination - Jiujing Xu; Cheng Chen; Zhiyu Zhao; Leihong Zhao; Wei Yu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Counter-cation engineering in polyoxovanadate cathodes: Unlocking superior zinc-ion storage stability via NH4+ induced hydrogen bond networks - Tiantian Guan; Chunxi Ren; Kunxuan Li; Yu Zhang; Fan Yang; Lei Wang; Qing Han; Xuejing Qiu; Lingling Xie; Hongjun Chen; Xiaobo Ji; Jianmin Ma; et al. (Chemical Engineering Journal, 2026)

Multiscale thermodynamic insights into membrane fouling control by biochar-activated peroxymonosulfate pretreatment: Synergy of oxidation and adsorption - Mingjing Xie; Wenfa Yang; Xiaoni Zhou; Biyan Wang; Jiaqi Liu; Xiao Xu; Liguo Shen; Hanmin Zhang; Meijia Zhang; Wei Yu; Jiaheng Teng; Hongjun Lin; et al. (Water Research, 2026)

Urbanization increases the impact of micropollutants on riverine planktonic food web - Bob Adyari; Lanping Zhang; Francisco J.A. Nascimento; Dandan Izabel-Shen; Yiqing Zhang; Meixian Cao; Jianjun Wang; Hongjun Li; Qian Sun; Chang-Ping Yu; Anyi Hu (Journal of Hazardous Materials, 2026)

Electroactivated cobalt-cobalt Prussian blue analog composite membrane for rapid persulfate-driven antibiotic degradation and fouling mitigation - Xiaoyue Yao; Hao Wang; Jingjing Liu; Yu Wang; Xuewen Tang; Hongjun Lin; Leihong Zhao; Bisheng Li; Renjie Li (Chemical Engineering Journal, 2026)

Alternating current or direct current: Which is better for electrochemical membrane separation water purification system? - Zhen Qiu; Jiujing Xu; Cheng Chen; Wei Yu; Bisheng Li; Liguo Shen; Bing Yu; Huajun Feng; Hongjun Lin (Chemical Engineering Journal, 2026)

Upper-bound limit analysis of near-fault jointed slopes stability based on the pulse-like ground motion and slope surface concave convex characteristics: a case study - Dejian Li; Hongjun Guo; Junwen Fu; Yingbin Zhang; Qiangshan Yu (Bulletin of Engineering Geology and the Environment, 2026)

Real-time soil moisture mapping using scalable RF sensor networks - Hongjun Yu; Erik Muller; Alex Mcbratney; Salah Sukkarieh (Computers and Electronics in Agriculture, 2025)

A heterogeneous sensing system for soil moisture mapping in agricultural environments - Thien Hoang Nguyen; Hongjun Yu; Erik Muller; Sarah Askey; Martijn van der Markt; Salah Sukkarieh (Computers and Electronics in Agriculture, 2025)

A modified curve number method for runoff prediction of different vegetation types at the slope scale in China - Jinle Yu; Hongjun Chen; Miaomiao Wang; Jiachi Bao; Wenyi Song; Xitong He; Wenhai Shi (Soil and Tillage Research, 2025)

Crossflow-induced vibration of a near-wall cylinder behind another of smaller diameter - Guanghao Chen; Md. Mahbub Alam; Yu Zhou; Hongjun Zhu; Chunning Ji; Junlei Wang; Md Islam; Mostafa Zeinoddini (Ocean Engineering, 2025)

Submarine groundwater discharge derived metal elements fluxes in a seawater intrusion influenced area - Yancheng Wang; Guangquan Chen; Wenzhe Lyu; Xinbin Zhao; Chutima Boonyaridsripong; Shengfa Liu; Hongjun Yu; Xingyong Xu (Journal of Environmental Sciences, 2025)

Thiol-ene click synthesis of a novel alginate-derived adsorbent: Synergistic adsorption and mechanistic investigation of dye and antibiotic - Xinyi Lu; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Guanhua Jin; Leihong Zhao; Saleem Raza; Liguo Shen (Desalination, 2025)

Chemical and microbial mechanism governing simultaneous nitrogen and phosphorus removal by anammox-hydroxyapatite granules - Shen Cui; Shenghao Ji; Hongjun Zhao; Tianyi Zhang; Yu-You Li (Chemical Engineering Journal, 2025)

Soil carbon dioxide dynamics in deep profiles under erosional and depositional conditions on the Chinese Loess Plateau - Jiachi Bao; Tiantian Chen; Wenyi Song; Miaomiao Wang; Hongjun Chen; Jinle Yu; Wenhai Shi (CATENA, 2025)

Deep Learning in Slope Stability Analysis: Evolution, Challenges, and Future Directions - Dejian Li; Zheng Wang; Hongjun Guo; Yingbin Zhang; Xiao Cheng; Qiangshan Yu (Geotechnical and Geological Engineering, 2025)

MAZ-mediated LAMA5 transcription activation promotes gastric cancer progression through the STAT3 signaling - Yu Wang; Jiazhong Xu; Hongxia Zhang; Xiaobo Guo; Hongjun Liu; Qinhui Sun (Functional & Integrative Genomics, 2025)

Decoupling and decomposition analysis of industrial carbon emissions, and projection of its future trends: A case study of Quanzhou, China - Yanxi Tang; Jing Xu; Muping Shen; Jiachang Zuo; Fengyi Yu; Yingmao Tang; Tingting Liu; Hongjun Jin; Yongjin Luo; Qingrong Qian; Qinghua Chen (Environment, Development and Sustainability, 2025)

Molecular insights in outstanding performance of Ca2+ bridging MXene/Sodium alginate composite membranes - Hua Li; Hongjun Lin; Saleem Raza; Zhiyu Zhao; Siyuan Chen; Yue Wang; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Water Research, 2025)

Advanced membrane technology for per- and polyfluoroalkyl substances removal: Innovations in membrane materials and hybrid systems - Wei Yu; Jiaheng Teng; Xiang Cai; Liguo Shen; Genying Yu; Bisheng Li; Leihong Zhao; Hongjun Lin (Journal of Environmental Management, 2025)

A novel fully coupled thermal-hydraulic-mechanical model for hydrogen storage in depleted gas reservoirs - Jing Fu; Keni Zhang; Hongjun Yin; Philip H. Winterfeld; Yu-Shu Wu (Gas Science and Engineering, 2025)

Diatomic catalytic sites on MOF-derived architecture towards effective H2 production - Hongjun Dong; Hansong Cheng; Yun Wang; Zuoyi Liu; Deping Wang; Liqiu Zhang; Yangyang Yu; Chunmei Li (Chemical Engineering Journal, 2025)

Double cross-linking architectonics membranes for high-efficiency oil-water separation and the mechanistic investigation - Yue Wang; Hongjun Lin; Siyuan Chen; Hua Li; Zhiyu Zhao; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2025)

Molecular design of polyoxovanadate cathodes for advanced AZIBs: Multielectron redox chemistry and structural engineering - Yu Zhang; Tiantian Guan; Fan Yang; Qing Han; Lingling Xie; Xuejing Qiu; Lei Wang; Hongjun Chen; Yuling Wang; Xiaobo Ji; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2025)

3D-printed super-wetting membranes with in situ grown MOF for efficient oil-water separation - Siyuan Chen; Zhiyu Zhao; Cheng Chen; Wei Yu; Xinchun Lu; Yue Wang; Hua Li; Qianqian Zeng; Hongjun Lin; Leihong Zhao; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2025)

Facile fabrication of MnCO3 and covalent organic framework on the surface of MXene with sodium alginate hydrogel for effective photocatalytic eradication of disinfected byproducts - Saleem Raza; Cheng Chen; Wei Yu; Muslim Raza; Malik Taj Ahmad; Nisha Singh; Liguo Shen; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Novel CoMo-LDH integration enhanced permeability and self-cleaning of MXene-based membrane for efficient water treatment - Qianqian Zeng; Zhiyu Zhao; Yue Wang; Siyuan Chen; Hua Li; Cheng Chen; Wei Yu; Jiaheng Teng; Hongjun Lin; Yu Yang; Liguo Shen (Chemical Engineering Journal, 2025)

Stable molecular-bridged graphene oxide membrane with bioinspired hydrophilic water inlets for ultrafast molecular separation - Boya Wang; Cheng Chen; Wei Yu; Jiujing Xu; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2025)

Optimization of up-flow velocity enhances the performance of partial denitrification/anammox process in expanded granular sludge bed reactor based on the formation of hydroxyapatite - Shenghao Ji; Shen Cui; Hongjun Zhao; Haojie Qin; Yu Qin; Yujie Chen; Yu-You Li (Chemical Engineering Journal, 2025)

Performance and microbial adaptation of a continuous granular sludge-type nitritation process facing the decreasing temperature condition until 5 ℃ - Hongjun Zhao; Yan Guo; Ze Zhang; Qianqian Li; Xiaona Wang; Yuanyuan Ren; Yu-You Li; Qunhui Wang (Bioresource Technology, 2025)

Controls of paleosedimentary environments and anthropogenic activities on coastal groundwater salinization: A case study of Laizhou Bay, China - Zhen Cui; Guangquan Chen; Xin Shan; Haitao Zhang; Qingjie Zhou; Tengfei Fu; Hongjun Yu; Xingyong Xu; Shenliang Chen (Marine Geology, 2025)

Competitive effects and environmental factors driving heavy metal leaching in stabilized municipal solid waste incineration fly ash under extreme conditions - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Chuanfu Wu; Shu Liu (Journal of Hazardous Materials, 2025)

Membrane technology for microplastic removal: Microplastic occurrence, challenges, and innovations of process and materials - Zhuoran Lin; Xingyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Wei Yu; Bisheng Li; Leihong Zhao; Mingyi Ying (Chemical Engineering Journal, 2025)

Deciphering the nexus of soluble microbial products (SMPs) and membrane fouling: Roles, mechanisms, and control strategies - Xinyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Jiaheng Teng; Meijia Zhang; Bisheng Li; Leihong Zhao; Die ling Zhao; Cheng Chen (Chemical Engineering Journal, 2025)

Bio-derived carboxymethyl cellulose-graft-gallic acid antiscalant with remarkable antibacterial activity for reverse osmosis scaling and biofouling control - Liping Xiong; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Liguo Shen (Water Research, 2025)

Alternating current electrochemistry for energy-efficient contaminant removal and resource recovery in water treatment: A critical review - Chengyue Yu; Cheng Chen; Mingzhu Zhou; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2025)

Rhubarb with Different Cooking Methods Restored the Gut Microbiota Dysbiosis and SCFAs in Ischemic Stroke Mice - Jing Xu; Taotao Liu; Fuzhu Pan; Xuan Ao; Lan Wang; Rixin Liang; Yuxin Lei; Yurong Ding; Miao Yu; Li Li; Hongjun Yang (Molecular Neurobiology, 2025)

Reproducing nonlinear ground response and pore pressure variations using in-situ soil properties - Hongjun He; Yu Miao; Suyang Wang (Soil Dynamics and Earthquake Engineering, 2025)

Cu-Thioamide coordination polymers derived Cu-S catalysts for CO2 electroreduction to formate - Honglin Li; Xin Zhang; Yuanyuan Wen; Jingyuan Li; Yu Liu; Hongjun Mao; Hongman Sun; Jingbin Zeng; Zifeng Yan (Fuel, 2025)

Hierarchical Adaptive Fixed-Time Formation Control for Multiple Underactuated Autonomous Underwater Vehicles Under Uncertain Disturbances and Input Saturation - Jiacheng Chang; Lanyong Zhang; Yifan Tan; Xue Fu; Hongjun Yu (Journal of Marine Science and Engineering, 2025)
Recent advances in multiple autonomous underwater vehicles (AUVs) have highlighted formation control as a critical challenge for underwater collaborative operations. To address the inherent coupling between formation coordination and individual control in conventional approaches, this paper proposes a novel hierarchical framework of adaptive fixed-time formation control for multiple underactuated AUVs. This framework decouples AUVs’ formation requirements and individual control challenges into two distinct layers: the Collision-free Formation Trajectories Generation (CFTG) Layer and the Adaptive Trajectories Tracking (ATT) Layer. In the CFTG Layer, a consensus-based controller is developed to generate the desired trajectories for the AUVs to meet the requirements of complex formation tasks. And an improved artificial potential field method is proposed to ensure AUVs can reach the target point when the target is close to obstacles. In the ATT Layer, an auxiliary compensation system is designed to address the issue of input saturation. Furthermore, the adaptive fixed-time controllers are proposed to handle the uncertain parameters in the model, enabling underactuated AUVs to track the desired trajectory precisely. Both layers guarantee fixed-time convergence to increase the convergence speed. Simulations are conducted to demonstrate the effectiveness and better performance of the proposed method.

Chelation treatment for heavy metals in municipal solid waste incineration fly ash: 300-Day study on stability and environmental risk - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Qunhui Wang; Chuanfu Wu (Waste Management, 2025)

Enhancing oil/water emulsion separation with inkjet printed beetle-inspired zeolitic imidazolate framework-67 modified membranes - Xinyu Hu; Hongli Xie; Hao Wang; Liguo Shen; Renjie Li; Hongjun Lin; Leihong Zhao; Genying Yu (Desalination, 2025)

A modified curve number method for runoff prediction of different soil types in China - Miaomiao Wang; Yangdong Zhao; Wenhai Shi; Jinle Yu; Tiantian Chen; Jiachi Bao; Wenyi Song; Hongjun Chen (CATENA, 2025)

Membrane fouling behaviors of microplastic in coagulation-ultrafiltration process: Role of surface functional groups - Yue Shen; Tao Jian; Genying Yu; Hongjun Lin; Xiang Cai; Liguo Shen; Zengjian Zhao; Leihong Zhao; Meijia Zhang; Die Ling Zhao; Bisheng Li (Chemical Engineering Journal, 2025)

SIRT3 regulates PFKFB3-mediated glycolysis to attenuate cisplatin-induced ototoxicity both in vivo and in vitro - Wei Tang; Shimin Zong; Peiyu Du; Xuan Yu; Ting Li; Bo Liu; Yu Zhong; Wenyang Lei; Wenting Yu; Hongjun Xiao (Archives of Toxicology, 2025)

Flow-induced vibrations of a wake cylinder at a low mass-damping ratio - Jian Liu; Md. Mahbub Alam; Hongjun Zhu; Md Islam; Yu Zhou; Mostafa Zeinoddini (Ocean Engineering, 2025)

Green β-cyclodextrin interlayered crumpled polyamide membranes for effective desalination - Jian Yu; Ling Zhang; Hongguang Sun; Renjie Li; Die Ling Zhao; Liguo Shen; Hongjun Lin; Yang Jiao; Yanchao Xu (Desalination, 2025)

Mechanical Properties and Microstructure Characteristics of Submerged Cement-Based Stabilized Marine Soft Clay Enhanced with ISS and PAM - Chenghao Zhu; Peng Yu; Zixian Guo; Qigang Wang; Hongjun Liu (Journal of Ocean University of China, 2025)

Illuminating for purity: Photocatalytic and photothermal membranes for sustainable oil-water separation - Hongyuan Zhu; Zhenyu Guo; Wei Yu; Shasha Yuan; Liguo Shen; Die Ling Zhao; Hongjun Lin (Water Research, 2025)

The relationship between high-quality development and ecosystem health in China's urban agglomerations - Bin Yang; Xiaohan Ma; Jirong Li; Haochen Yu; Hongjun Sui; Fu Chen; Li Tan (Journal of Environmental Management, 2025)

A novel method to improve the anti-ageing ability of bitumen by organic LDHs/SBS composite: Preparation, performance evaluation and mechanism analysis - Canlin Zhang; Shuai Yang; Ting Wang; Song Xu; Peng Jin; Hongjun Dong; Yi Zhang; Yu Chen (Fuel, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Corrigendum to ‘Exploring the maximum nitrite production rate through the granular sludge-type reactor to match the needs of anammox process realizing efficient nitrogen removal’ [Environ. Res. 255 (2024) 119158] - Hongjun Zhao; Yan Guo; Xiaona Wang; Haishu Sun; Ming Gao; Chuanfu Wu; Shuang Li; Yu-you Li; Qunhui Wang (Environmental Research, 2025)

An improved curve number for runoff prediction under different vegetation pattern at slope scale in China - Wenhai Shi; Miaomiao Wang; Jiachi Bao; Jinle Yu; Tiantian Chen; Wenyi Song; Hongjun Chen (CATENA, 2025)

Investigating small-strain site response using inverse soil dynamic parameters from downhole arrays - Hongjun He; Xiaohua Ke; Yu Miao; Chenxi Miao (Soil Dynamics and Earthquake Engineering, 2025)

Strengthening peroxymonosulfate activation via cotton-derived carbon: Pathway transformation from radical to non-radical - Runbin Su; Yonglin Ma; Lei Liu; Qiangshun Wu; Du Fu; Yu Li; Hongjun Lin; Xiaoxuan Wei; Muhammad Saboor Siddique; Jianrong Chen; Xi-Lin Wu (Journal of Cleaner Production, 2025)

Microplastic transport and ecological risk in coastal intruded aquifers based on a coupled seawater intrusion and microplastic risk assessment model - Guangquan Chen; Yinqiao Zou; Guiyao Xiong; Yancheng Wang; Wenqing Zhao; Xingyong Xu; Xiaobin Zhu; Jichun Wu; Fan Song; Hongjun Yu (Journal of Hazardous Materials, 2024)

A novel application of industrial waste bischofite for the anti-aging property of asphalt: Synthesis of organic layered double hydroxide and performance evaluation - Hongjun Dong; Canlin Zhang; Yiwei Weng; Ting Wang; Song Xu; Shijie Ma; Shuai Yang; Yu Chen (Journal of Cleaner Production, 2024)

Polyimide-multiwalled carbon nanotubes composite as electrochemical sensing platform for the simultaneous detection of nitrophenol isomers - Jianzheng Wang; Chunying Liu; Ziao Di; Jiayu Huang; Hongjun Wei; Minjie Guo; Xiaoliang Yu; Nan Li; Jin Zhao; Bowen Cheng (Chemosphere, 2024)

Activation of peroxymonosulfate by novel magnetically recyclable CoFe2O4/MXene quantum dots composites for rapid degradation of tetracycline: Synergistic performance and mechanisms - Zhenyu Guo; Haiyi Jin; Hongyu Sun; Bisheng Li; Huadong Yu; Die Ling Zhao; Hongjun Lin (Journal of Environmental Management, 2024)

Nonlinear seismic response analysis of liquefiable sites based on effective stress method - Hongjun He; Hanwen Ji; Yang Shi; Xiaohua Ke; Yu Miao (Computers and Geotechnics, 2024)

Optimization of microalgal-bacterial consortium flocculation through chitosan-diatomite composite materials: A sustainable approach to biomass harvesting - Yu Zhao; Qian Lei; Jiaheng Teng; Xiu Zhang; Hongjun Lin; Meijia Zhang (Chemical Engineering Journal, 2024)

Nonnegligible contribution of terrigenous sediment inputs from local small watersheds to west regions of the Pearl River Estuary, northern South China Sea shelf - Chenjian He; Tingping Ouyang; Mingkun Li; Shanying Zhu; Mingjie Yu; Shasha Peng; Zhaoyu Zhu; Yunpeng Wang; Hongjun Chen; Chengjing Tian (Marine Geology, 2024)

Insights into in situ surface reconstruction in cobalt perovskite oxides for enhanced catalytic activity - Yanyu Jin; Hongjun Cheng; Qibao Wang; Xiaoqing Liu; Shengpeng Mo; Bin Zhou; Yue Peng; Yu Wang; Wenzhe Si; Junhua Li (Journal of Hazardous Materials, 2024)

TC activity affected the northern sea of the Shandong Peninsula over the past 1500 years and its driving mechanism - Wenzhe Lyu; Tengfei Fu; Zhen Cui; Yancheng Wang; Wenquan Liu; Xingyong Xu; Hongjun Yu (Marine Geology, 2024)

Exploring the maximum nitrite production rate through the granular sludge-type reactor to match the needs of anammox process realizing efficient nitrogen removal - Hongjun Zhao; Yan Guo; Xiaona Wang; Haishu Sun; Ming Gao; Chuanfu Wu; Shuang Li; Yu-you Li; Qunhui Wang (Environmental Research, 2024)

Sedimentary evolution of the East China Sea with implications for the relationship between the East Asian winter and summer monsoon over the past 6.3 ka - Wenzhe Lyu; Tengfei Fu; Guangquan Chen; Qiao Su; Wenquan Liu; Yancheng Wang; Zhen Cui; Hongjun Yu; Xingyong Xu (Journal of Asian Earth Sciences, 2024)

Innovative treatment of industrial effluents through combining ferric iron and attapulgite application - Zhenxiang Pan; Bizhen Zeng; Liguo Shen; Jiaheng Teng; Tongli Lai; Leihong Zhao; Genying Yu; Hongjun Lin (Chemosphere, 2024)

Progress and perspective on the topological spin textures in two-dimensional van der Waals magnets - Hongjun Xu; Yizhou Liu; Giovanni Finocchio; Kang L. Wang; Guoqiang Yu (Science Bulletin, 2024)

Chronic exposure to gestodene impairs reproductive system in adult female zebrafish (Dania rerio) - Hong Zou; HongJun Yu; YunYi Huang; YanFang Guo; MeiXin Ye; LiPing Hou (Chemosphere, 2024)

Selenium in plants: A nexus of growth, antioxidants, and phytohormones - Sufian Ikram; Yang Li; Chai Lin; Debao Yi; Wang Heng; Qiang Li; Lu Tao; Yu Hongjun; Jiang Weijie (Journal of Plant Physiology, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

Mg2+ addition: Unlocking optimized treatment performance and anti-fouling property in microalgal-bacterial membrane bioreactors - Fei Huang; Yu Zhao; Shilei Chen; Hongjun Lin; Jiaheng Teng; Xiang Cai; Meijia Zhang (Science of The Total Environment, 2024)

Biotoxicity dynamic change and key toxic organics identification of coal chemical wastewater along a novel full-scale treatment process - Weiwei Ma; Xiaoqi Zhang; Hongjun Han; Xueqing Shi; Qiaoping Kong; Tong Yu; Fei Zhao (Journal of Environmental Sciences, 2024)

Emerging disinfection byproducts 3-bromine carbazole induces cardiac developmental toxicity via aryl hydrocarbon receptor activation in zebrafish larvae - Yingying Liu; Xudong Jin; Yanan Ye; Zeqiong Xu; Zhongkun Du; Huachang Hong; Haiying Yu; Hongjun Lin; Xianfeng Huang; Hongjie Sun (Environmental Pollution, 2024)

Advances in synthesis and application of amphoteric polymer-based water treatment agents - Wei Yu; Liping Xiong; Jiaheng Teng; Cheng Chen; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Desalination, 2024)

Stabilization of heavy metals in municipal solid waste incineration fly ash using organic chelating agents: Insight into risk assessment and function mechanism - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Amirhomayoun Saffarzadeh; Xiaona Wang; Chuanfu Wu; Qunhui Wang (Science of The Total Environment, 2024)

Synthesis of organic layered double hydroxide from waste bischofite and its application on ageing resistance of asphalt - Canlin Zhang; Hongjun Dong; Ting Wang; Yifei Li; Song Xu; Yun Que; Yu Chen (Fuel, 2024)

Effects of childhood maltreatment and major depressive disorder on functional connectivity in hippocampal subregions - Huiqin Nie; Tong Yu; Yurong Zou; Yuhong Li; Juran Chen; Jinrou Xia; Qianyi Luo; Hongjun Peng (Brain Imaging and Behavior, 2024)

Harnessing diurnal dynamics: Deciphering the interplay of light cycles on algal-bacterial membrane bioreactors - Sihan Cheng; Yuwei Zhang; Yu Zhao; Xin Hu; Hongjun Lin; Jiaheng Teng; Meijia Zhang (Science of The Total Environment, 2024)

Atomically dispersed dual-atom catalysts: A new rising star in environmental remediation - Xialiang Jiang; Cheng Chen; Junjie Chen; Shuning Yu; Wei Yu; Liguo Shen; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Science of The Total Environment, 2024)

Experimental study of structure dimensions effects on local scour of submerged compound suction anchor foundation - Chenghao Zhu; Wenyu Wu; Xiaoli Liu; Hongjun Liu; Ruigeng Hu; Peng Yu (Ocean Engineering, 2024)

Experimental and numerical investigation on the impact of MS2AF on local scour protection performance - Chenghao Zhu; Qiheng Li; Jianguo Zheng; Hongjun Liu; Peng Yu (Ocean Engineering, 2024)

Seawater intrusion-triggered high fluoride groundwater development on the eastern coast of China - Tengfei Fu; Yushan Fu; Chenzhe Li; Minxing Dong; Chen Qi; Zhenyan Wang; Guangquan Chen; Qiao Su; Xingyong Xu; Hongjun Yu (Environmental Science and Pollution Research, 2024)

Groundwater salinization under the influence of paleo sea-level fluctuation: a case study in southern Laizhou Bay, China - Zhen Cui; Guangquan Chen; Shenliang Chen; Hongjun Yu; Keke Chen; Baichuan Ran; Tengfei Fu; Wenzhe Lyu; Yancheng Wang; Xueyan Jiang; Xihuang Zhong (Frontiers in Marine Science, 2024)
The groundwater environment in low-lying coastal regions is significantly impacted by global sea-level fluctuation. In Laizhou Bay, three large-scale transgressions have occurred since the late Pleistocene, resulting in the transformation of ancient seawater into brine. This brine has become a major contributor to groundwater salinity in the area. This study establishes a correlation between groundwater occurrence and paleoclimate changes in Laizhou Bay using borehole sediment data. The source and mechanism of groundwater salinity are analyzed based on sediment pore water characteristics and hydrogen and oxygen isotopes. The study reveals that the stratigraphic structures in the area consist of four layers: a Holocene transgressive layer, a continental confining bed from the late Pleistocene, a Cangzhou transgressive layer from the late Pleistocene, and a fluvial aquifer from the middle Pleistocene. All aquifers in the study area have been infiltrated by modern seawater, with the uppermost Holocene aquifer influenced by evaporation and leaching processes, the central late Pleistocene aquifer remaining relatively stable, and the lower middle Pleistocene aquifer affected by subsurface low salinity runoff and exhibiting an increasing trend with depth. Given the presence of numerous hydrogeological environments globally that are similar to the study area, the obtained mechanisms of groundwater salinization in this study will provide theoretical support for groundwater management in similar regions worldwide.

Nitro substituent caused negative impact on occurrence and development of atherosclerotic plaque by PM2.5-bound polycyclic aromatic compounds - Yu Zhang; JingBo Zhao; Qian Hu; HongJun Mao; Ting Wang (Science of The Total Environment, 2024)

Overview of enhancing biological treatment of coal chemical wastewater: New strategies and future directions - Weiwei Ma; Xiaoqi Zhang; Hongjun Han; Xueqing Shi; Qiaoping Kong; Tong Yu; Fei Zhao (Journal of Environmental Sciences, 2024)

Understanding the degradation mechanisms of cyanide and starch in cassava flour during extrusion processing - Mingming Qi; Jialin Song; Lijun Jiang; Luxia Li; Mei Xu; Yueming Li; Shifeng Yu; Hongjun Li (Innovative Food Science & Emerging Technologies, 2024)

The stable operation of nitritation process with the continuous granular sludge-type reactor and microbial community analysis - Hongjun Zhao; Yan Guo; Ze Zhang; Haishu Sun; Xiaona Wang; Shuang Li; Jianbo Liao; Yu-You Li; Qunhui Wang (Chemosphere, 2023)

Seasonal changes driving shifts in microbial community assembly and species coexistence in an urban river - Wangkai Fang; Tingyu Fan; Shun Wang; Xiaokun Yu; Akang Lu; Xingming Wang; Weimin Zhou; Hongjun Yuan; Lei Zhang (Science of The Total Environment, 2023)

Anaerobic biodegradation of azo dye reactive black 5 by a novel strain Shewanella sp. SR1: Pathway and mechanisms - Jiale Liu; Lu Fan; Wenjun Yin; Shusheng Zhang; Xiaomei Su; Hongjun Lin; Haiying Yu; Zhenghai Jiang; Faqian Sun (Journal of Environmental Management, 2023)

Effects of replacement partial sodium chloride on characteristic flavor substances of bacon during storage based on GC×GC-MS and non-targeted metabolomics analyses - Jinggang Ruan; Zhicheng Wu; Jingbing Xu; Yiru Yu; Yong Tang; Xinrui Xie; Jiaxin Chen; Zhaoming Wang; Dong Zhang; Jie Tang; Hongjun Li (Food Chemistry, 2023)

Assembly and phylogenetic analysis of the mitochondrial genome of endangered medicinal plant Huperzia crispata - Yu Cao; Dengpan Yin; Bo Pang; Haibo Li; Qiao Liu; Yufeng Zhai; Nan Ma; Hongjun Shen; Qiaojun Jia; Dekai Wang (Functional & Integrative Genomics, 2023)

Unlocking the potential of resuscitation-promoting factor for enhancing anaerobic microbial dechlorination of polychlorinated biphenyls - Zhen Han; Aiqin Hou; Xiaolin Cai; Mengqi Xie; Faqian Sun; Chaofeng Shen; Hongjun Lin; Haiying Yu; Xiaomei Su (Science of The Total Environment, 2023)

Glyphosate-based herbicide (GBH) challenged thermoregulation in lizards (Eremias argus), compensatory warming could mitigate this effect - Simin Yu; Yufan Nie; Zikang Wang; Luyao Zhang; Rui Liu; Yuping Liu; Hongjun Zhang; Wentao Zhu; Mingqi Zheng; Jinling Diao (Science of The Total Environment, 2023)

Wall-proximity effects on vortex-induced vibrations of a circular cylinder - Guanghao Chen; Md. Mahbub Alam; Yu Zhou; Chunning Ji; Hongjun Zhu (Ocean Engineering, 2023)

Novel strategy to enhance the biological treatment of coal chemical wastewater by nano-zero valent iron loaded fly ash-based activated carbon assisted activated sludge process - Weiwei Ma; Xiaoqi Zhang; Hongjun Han; Xueqing Shi; Qiaoping Kong; Tong Yu; Fei Zhao (Environmental Science and Pollution Research, 2023)

Configuration modulation of vermiculite by exfoliation coupled Cu(II) anchoring for boosting removal of tetracycline via synergy of adsorption and photocatalysis - Ping Zhang; Mingxue Xiang; Wei Jiang; Huiling Liu; Yu Chen; Ying Fang; Longyong Wu; Hongjun Guo; Yufei Wang (Chemical Engineering Journal, 2023)

Solidification/stabilization and risk assessment of heavy metals in municipal solid waste incineration fly ash: A review - Ze Zhang; Chutong Zhao; Yi Rao; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Chuanfu Wu; Qunhui Wang (Science of The Total Environment, 2023)

Clinical, epidemiological, and genotypic characteristics of rotavirus infection in hospitalized infants and young children in Yunnan Province - Hongjun Jiang; Yu Zhang; Xiaoyan Xu; Xiaohan Li; Yi Sun; Xin Fan; Ya Xu; Ting Su; Guiqian Zhang; Ziqin Dian (Archives of Virology, 2023)
Rotaviruses are the most important pathogenic cause of non-bacterial diarrhea in infants and children. Approximately 60% of hospital admissions for acute diarrhea worldwide are caused by rotavirus infection. Rotavirus infection and hospitalization among children in China are a social burden, resulting in economic loss. The prevalence and geographical distribution of rotavirus genotypes is variable, partially due to population migration. Due to the unique geographical conditions and climate in Yunnan Province, several viruses with new genotypes have emerged, and multiple genotypes have become co-epidemic. In this study, rotavirus infection screening and genetic characterization of epidemic strains were performed in 149,492 infants and children admitted to hospitals in six representative prefectures in Yunnan Province between 2019 and 2021. The prevalence of rotavirus infection was 13.39% and was highest in January and lowest in September. G9P[8] was the main epidemic rotavirus genotype. Other epidemic genotypes included G2P[4], G8P[8], G9P[4], G2P[8], G3P[8], G4P[8], G3P[4], and G4P[6]. Phylogenetic analysis revealed that locally epidemic strains were influenced by importation of strains from neighboring provinces and other Asian countries. These findings provide a scientific basis for rotavirus prevention and control and lay a foundation for preliminary studies to establish a rotavirus surveillance network in Yunnan Province.

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Simulation of transport mechanism of radium isotopes in aquifer on the southern coast of Laizhou Bay - Yancheng Wang; Guangquan Chen; Hongjun Yu; Xingyong Xu; Yinqiao Zou; Wenqing Zhao; Weitao Han; Wenzhe Lyu; Zhen Cui; Runtian Ding (Acta Oceanologica Sinica, 2023)

Softening/Hardening Damage Model and Numerical Implementation of Seabed Silt-Steel Interface in Yellow River Underwater Delta - Peng Yu; Honghua Liu; Lin Geng; Shuai Wang; Yang Yu; Chenghao Zhu; Qi Yang; Hongjun Liu; Yong Guan (Journal of Marine Science and Engineering, 2023)
The interaction between soil and structure is a research hotspot in ocean engineering, and the shear performance of interfaces is an essential factor affecting the bearing capacity of offshore structures. Taking the Yellow River Underwater Delta as the research area, the Softening/Hardening damage model of the silt–steel interface and the determination method of model parameters are proposed based on the statistical damage theory. Through the interface monotonic shear test under the conditions of different normal stress, roughness and water content, the shear mechanical properties and volumetric deformation laws on the silt–steel interface are analyzed, and the damage model parameters are obtained. Finally, a FRIC subroutine for the damage model was developed based on ABAQUS. The research results indicate the following: (1) The interface between silt and steel exhibits two characteristics, softening/hardening and shear shrinkage/expansion, under different conditions. Roughness significantly impacts interfacial cohesion, while water content mainly affects the internal friction angle. (2) The softening model based on the classic rock damage model can better simulate the stress–strain relationship of the silt–steel interface under high normal stress and low water content. In contrast, the hardening model based on the classic hyperbola model can better simulate the stress–strain relationship under low normal stress and high water content. The calculated results of the softening/hardening model agree with the experimental results, and the model has 7 parameters. (3) The developed FRIC subroutine can effectively simulate the nonlinear mechanical behavior of the interface between silt and steel. The research results provide a reference for exploring the stability analysis of offshore structures considering interface weakening effects.

Physical activity intensity, frequency, duration, volume and the risk of possible sarcopenia in middle-aged and older adults - Xiaoguang Zhao; Hongjun Zhang; Jiabin Yu; Zhexiao Zhou; Jin Wang (GeroScience, 2023)

Deformation analysis of underwater shield tunnelling based on HSS model parameter obtained by the Bayesian approach - Yao Lu; Peng Yu; Yan Zhang; Jian Chen; Tao Liu; Han Wang; Hongjun Liu (Frontiers in Marine Science, 2023)
Deformation analysis and control of underwater large-diameter shield tunnels is a prerequisite for safe tunnel construction. Reasonable selection of constitutive model and its parameters is the key to accurately predicting the deformation induced by underwater shield tunnelling. In this paper, the finite element analysis of cavity expansion during the piezocone penetration test (CPTU) based on the hardening soil model with small strain stiffness (HSS) model was carried out, and the correlation model of the normalized cone tip resistance Q with the reference secant modulus E 50 ref and the effective internal friction angle φ ’ was established and verified using mini CPTU chamber test. Then, a Bayesian probability characterization approach for E 50 ref of silty clay based on CPTU was proposed. Furthermore, the deformation analysis of Jinan Yellow River tunnel crossing the south embankment was carried out to verify the reliability of the proposed approach. The good agreement between the field measurement and numerical simulation confirms that the parameters obtained by the Bayesian approach are reliable. Finally, a sensitivity analysis was performed to study the law of riverbed settlement induced by underwater large-diameter shield tunnelling. The results show that the increasing support pressure could effectively reduce the riverbed settlement, but there is an upper limit. The optimal support pressure of established model is between 0.45 MPa and 0.5 MPa. The uphill section causes greater riverbed settlement than the downhill section. Under the same condition, increasing buried depth and water level will lead to a more significant settlement.

Hydrochemical characteristics and quality assessment of groundwater in Guangxi coastal areas, China - Tengfei Fu; Chenzhe Li; Zhenyan Wang; Chen Qi; Guangquan Chen; Yushan Fu; Qiao Su; Xingyong Xu; Wenquan Liu; Hongjun Yu (Marine Pollution Bulletin, 2023)

Developmental dynamics and survival characteristics of the common horse bot flies (Diptera, Gasterophilidae, Gasterophilus) in desert steppe - Ke Zhang; Zhongrui Ju; Yu Zhang; Chen Wang; Shalitanati Mubalake; Dini Hu; Dong Zhang; Kai Li; Hongjun Chu (Veterinary Parasitology, 2023)

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

Study of spatialtemporal changes in Chinese forest eco-space and optimization strategies for enhancing carbon sequestration capacity through ecological spatial network theory - Shi Qiu; Minzhe Fang; Qiang Yu; Teng Niu; Hongjun Liu; Fei Wang; Chenglong Xu; Mingsi Ai; Jieyu Zhang (Science of The Total Environment, 2023)

Multi-omics analysis reveals copper-induced growth inhibition mechanisms of earthworm (Eisenia fetida) - Yanliang Zhang; Jinqi Zhao; Na Sa; Chenyu Huang; Wenyu Yu; Tianxiao Ma; Hongjun Yang; Fang Ma; Siqi Sun; Chaochun Tang; Weiguo Sang (Environmental Pollution, 2023)

Experimental Investigation on the Cyclic Shear Mechanical Characteristics and Dynamic Response of a Steel–Silt Interface in the Yellow River Delta - Peng Yu; Jie Dong; Yong Guan; Qing Wang; Shixiang Jia; Meijun Xu; Hongjun Liu; Qi Yang (Journal of Marine Science and Engineering, 2023)
The shear behavior and dynamic response of a steel–silt interface are significant for the safety and stability of offshore structures in the Yellow River Delta. A series of steel–silt interface cyclic shear tests under constant normal load conditions (CNL) were carried out to explore the effects of normal stress, shear amplitude, roughness, and water content on the interface shear strength, shear stiffness, and damping ratio using a large interface shear apparatus. The preliminary results showed that the amplitude of normal stress and shear amplitude affected the interface’s shear strength, stiffness, and damping ratio in a dominant manner. The roughness and water content were also crucial factors impacting the rule of shear strength, shear stiffness, and damping ratio, changing with the number of cycles. Under various scenarios, the steel–silt interface weakened distinctively, and the energy dissipation tended to be asymptotic with the cyclic shear.

Efficient oil-water emulsion treatment via novel composite membranes fabricated by CaCO3-based biomineralization and TA-Ti(IV) coating strategy - Hongli Xie; Binghong Chen; Hongjun Lin; Renjie Li; Liguo Shen; Genying Yu; Lining Yang (Science of The Total Environment, 2023)

Enhanced photocatalytic degradation of sulfamethazine by g-C3N4/Cu, N-TiO2 composites under simulated sunlight irradiation - Xiaolan Zeng; Shuang Shu; Yu Meng; Hongjun Wang; Yan Wang (Chemical Engineering Journal, 2023)

The coupling of persulfate activation and membrane separation for the effective pollutant degradation and membrane fouling alleviation - Mingzhu Zhou; Junjie Chen; Shuning Yu; Binghong Chen; Cheng Chen; Liguo Shen; Bisheng Li; Hongjun Lin (Chemical Engineering Journal, 2023)

A study on green technology efficiency of China’s marine ship industry chain based on meta-frontier framework and three-stage EBM model - Hongjun Guan; Yu Wang; Aiwu Zhao (Frontiers in Marine Science, 2022)
Under strict resource and environmental constraints, improving the overall green efficiency of the industrial chain is crucial to the sustainable development of the marine ship industry. Based on the data of 40 listed companies in the industry chain from 2015 to 2019, the meta-frontier framework and three-stage epsilon based measure (EBM) model are employed to study the green technical efficiency (GTE) in each link of the industry chain and the technical gap between each link. The impact of the external environment on GTE, the main reasons hindering the development of GTE, and the ways to improve GTE are also discussed for policy reference. The results show that: (1) under the meta-frontier, the GTEs of the whole industry chain and the composed links are all high and rising year by year. (2) There are obvious green technological development gaps among the links of the industry chain. The GTEs are ranked as the upstream>the downstream>the midstream. (3) The inefficiencies of green technology (GTEI) in the upstream and downstream of the industry chain come from endogenous hindrance, while the GTEI of the midstream is due to exogenous hindrance. (4) The external environment has a significant influence on the development of GTE in the industrial chain. Highly open and innovative external environment can effectively reduce the input redundancy. (5) After eliminating the external influencing factors and random interferences, the actual GTE of the industrial chain is only 0.4 or so, with more serious imbalance among the three links. Therefore, it is important for the marine ship industry chain to optimize the allocation of innovation resources and cultivate an open and shared innovation environment.

Analysis of Cyclic Shear Stress–Displacement Mechanical Properties of Silt–Steel Interface in the Yellow River Delta - Peng Yu; Jie Dong; Haisong Liu; Rui Xu; Rujie Wang; Meijun Xu; Hongjun Liu (Journal of Marine Science and Engineering, 2022)
Pile foundations of offshore structures are often subjected to cyclic loads under storm loads, thus reducing their vertical bearing capacity. Therefore, studying the cyclic shear behavior of the soil–structure interface is important for maintaining the stability of offshore structures. A series of cyclic shear tests of the silt–steel interface were carried out using a large interface shear apparatus. The effects of various factors (i.e., normal stress, shear displacement amplitude, roughness, and water content) on the shear stress characteristics of the silt–steel interface were investigated. The stress–displacement model of the cyclic shear silt–steel interface was deduced. The results showed that the shear stress at the silt–steel interface was softened, and the type of bulk deformation was shear shrinkage under cyclic shear. With the increase in shear amplitude, the hysteresis curve gradually developed from “parallelogram” to “shuttle” and “hysteresis cake”. With the increase in normal stress and roughness and the decrease in water content, the interfacial shear strength, volume displacements growth rate, and growth rate increased. The stress–displacement mathematical model of the silt–steel interface based on the modified hyperbolic model was in good agreement with the test data.

Aberrant brain connectivity is associated with childhood maltreatment in individuals with major depressive disorder - Qianyi Luo; Juran Chen; Yuhong Li; Zhiyao Wu; Xinyi Lin; Jiazheng Yao; Huiwen Yu; Huawang Wu; Hongjun Peng (Brain Imaging and Behavior, 2022)

Origin and Implications of Pollution in Coastal Groundwater of the Guangdong Province - Chenzhe Li; Tengfei Fu; Yushan Fu; Zhenyan Wang; Bin Li; Chen Qi; Guangquan Chen; Xingyong Xu; Hongjun Yu (Journal of Marine Science and Engineering, 2022)
The groundwater resource is crucial to the urbanization and industrialization in the Guangdong coastal area; the rapid development of Daya Bay has presented a challenge for the management of the groundwater quantity and quality. Therefore, a novel approach to hydrochemical analysis, which, combined with the health risk model and the water quality index (WQI), was used to explain the hydrochemistry characteristics and risks to human health of groundwater in the Guangdong coastal areas in addition to investigating the factors controlling groundwater quality. The results showed that the average concentration of total dissolved solids (TDS) in groundwater was 1935.26 mg/L and the quality of water was weakly alkaline. The dominant hydrochemical types of groundwater were identified to be Mg-HCO3 and Na-Cl·HCO3. The main factor influencing the hydrochemical composition was rock weathering, while the result of principal component analysis (PCA) shows seawater intrusion and anthropogenic inputs also have an effect on the water quality. The conclusions of the water quality assessment indicated that most of the groundwater samples were acceptable for drinking. However, both WQI and the non-carcinogenic hazard quotient (HQ) values indicated unacceptable risks in any area of Maoming, Zhanjiang and Shantou, and, according to the hazard index (HI) value, children in the study area are at more danger to health risks than adults. It is suggested that both groundwater salinization and nitrate pollution should be paid attention to when improving groundwater quality and exploring the sustainable utilization of groundwater resources.

PseAraUbi: predicting arabidopsis ubiquitination sites by incorporating the physico-chemical and structural features - Wei Wang; Yu Zhang; Dong Liu; HongJun Zhang; XianFang Wang; Yun Zhou (Plant Molecular Biology, 2022)

Two-stage hybrid network for segmentation of COVID-19 pneumonia lesions in CT images: a multicenter study - Yaxin Shang; Zechen Wei; Hui Hui; Xiaohu Li; Liang Li; Yongqiang Yu; Ligong Lu; Li Li; Hongjun Li; Qi Yang; Meiyun Wang; Meixiao Zhan; et al. (Medical & Biological Engineering & Computing, 2022)

The influence of socioeconomic and environmental determinants on acute myocardial infarction (AMI) mortality from the spatial epidemiological perspective - Yan Wang; Bin Guo; Lin Pei; Hongjun Guo; Dingming Zhang; Xuying Ma; Yan Yu; Haojie Wu (Environmental Science and Pollution Research, 2022)

Genome characterization and comparative analysis among three swimming crab species - Ming Liu; Shanshan Ge; Shivish Bhandari; Chunlei Fan; Yu Jiao; Chunlei Gai; Youhong Wang; Hongjun Liu (Frontiers in Marine Science, 2022)
In this study we sequenced the genomes of three economically important swimming crabs Portunus trituberculatus, Charybdis japonica , and Callinectes sapidus using the next-generation sequencing approach and made a basic assembly. The genomes of the three species are characterized with high heterozygosity (>1.2%) and high repeat content (>50%). Genome comparative analysis revealed 40 long conserved fragments (>5,000 bp) among the three species, most of them are involved in cardiac-related biological process. Relative higher genome similarity was found between P. trituberculatus and C. japonica that are belong to different subfamilies, compared to that between P. trituberculatus and C. sapidus which are from the same subfamily. It is inconsistent with their phylogenetic evolutionary trees inferred from previous mitochondrial DNA coding fragments and a conserved ANK2 protein fragment from this study. We speculated that the high genome similarity between P. trituberculatus and C. japonica might be attributed to their same inhabit range in which the genome is subject to the same environment selection, and the inconsistence between genome similarity and phylogenetic relationship is caused by the different evolutionary rates of coding DNA and non-coding DNA under environment selection.

Effect of dietary Bacillus licheniformis on growth, intestinal health, and resistance to nitrite stress in Pacific white shrimp Litopenaeus vannamei - Ying Fan; Xiaolu Wang; Youhong Wang; Haibin Ye; Xiaoqing Yu; Shuxian Wang; Jing Diao; La Xu; Chunlei Gai; Hongjun Liu; Danping Ma (Aquaculture International, 2021)

Combination of Polyethylene Glycol-Conjugated Urokinase Nanogels and Urokinase for Acute Ischemic Stroke Therapeutic Implications - Ding Nan; Haiqiang Jin; Di Yang; Weiwei Yu; Jingjing Jia; Zemou Yu; Hui Tan; Yongan Sun; Hongjun Hao; Xiaozhong Qu; Yining Huang (Translational Stroke Research, 2021)

TREM-1 aggravates chronic obstructive pulmonary disease development via activation NLRP3 inflammasome-mediated pyroptosis - Lijing Wang; Qiong Chen; Qiao Yu; Jian Xiao; Hongjun Zhao (Inflammation Research, 2021)

Scour Characteristics and Equilibrium Scour Depth Prediction around Umbrella Suction Anchor Foundation under Random Waves - Ruigeng Hu; Hongjun Liu; Hao Leng; Peng Yu; Xiuhai Wang (Journal of Marine Science and Engineering, 2021)
A series of numerical simulation were conducted to study the local scour around umbrella suction anchor foundation (USAF) under random waves. In this study, the validation was carried out firstly to verify the accuracy of the present model. Furthermore, the scour evolution and scour mechanism were analyzed respectively. In addition, two revised models were proposed to predict the equilibrium scour depth Seq around USAF. At last, a parametric study was carried out to study the effects of the Froude number Fr and Euler number Eu for the Seq. The results indicate that the present numerical model is accurate and reasonable for depicting the scour morphology under random waves. The revised Raaijmakers’s model shows good agreement with the simulating results of the present study when KCs,p

Do air pollutants as well as meteorological factors impact Corona Virus Disease 2019 (COVID-19)? Evidence from China based on the geographical perspective - Lin Pei; Xiaoxia Wang; Bin Guo; Hongjun Guo; Yan Yu (Environmental Science and Pollution Research, 2021)

Whole-genome analysis of the trimethylation of histone H3 lysine 4 and lysine 27 in two contrasting Tibetan hulless barley genotypes under salinity stress - Basang Yuzhen; Zha Sang; Wang Mu; Mingzhai Yu; Yulin Wang; Hongjun Yuan; Qijun Xu (Acta Physiologiae Plantarum, 2021)

Comparative analysis of H3K4 and H3K27 trimethylations in two contrasting Tibetan hulless barely varieties on powdery mildew infection - Sang Zha; Chunbao Yang; Xingquan Zeng; Zeqing Li; Yulin Wang; Hongjun Yuan; Mingzhai Yu; Qijun Xu (Journal of Plant Pathology, 2021)

Optimization of porcine embryonic germ cell culture system - Yang Li; Yu Qiao; Fei Li; Hongjun Wang; Xiao Dong (In Vitro Cellular & Developmental Biology - Animal, 2020)

Geochemistry and Petrogenesis of Volcanic Rocks from the Continent-Ocean Transition Zone in Northern South China Sea and Their Tectonic Implications - Yue Xu; Yaoming Yang; Hongjun Yu; Wei Gao; Xiangxing Gao; Baohua Liu; Xu Tian; Jichao Yang; Wenquan Zhang (Journal of Ocean University of China, 2020)

A new permeability predictive model based on NMR data for sandstone reservoirs - Hongjun Xu; Changxi Li; Yiren Fan; Falong Hu; Jun Yu; Jinyu Zhou; Changxue Wang; Chunmei Yang (Arabian Journal of Geosciences, 2020)

Phylogenetic analysis of the whole genome sequence of a dog lineage rabies virus detected from cattle in eastern China, 2019 - Kaihui Cheng; Huimeng Chu; Yachu Ren; Xiaoli Xie; Zhijun Yu; Hongjun Yang (Brazilian Journal of Microbiology, 2020)

Comprehensive Investigation and Assessment of Nutrient and Heavy Metal Contamination in the Surface Water of Coastal Bohai Sea in China - Heshan Lin; Hongjun Li; Xiaolong Yang; Zizhou Xu; Yindong Tong; Xingguang Yu (Journal of Ocean University of China, 2020)

Magnetic properties indicate the sources of hadal sediments in the Yap Trench, northwest Pacific Ocean - Yu Chen; Jichao Yang; Olusegun A. Dada; Yaomin Yang; Zhen Lin; Zhen Cui; Yue Xu; Hongjun Yu; Baohua Liu (Journal of Oceanology and Limnology, 2020)

High-resolution sequence divisions and stratigraphic models of the Amu Darya right bank - Chongyang Wu; Bingsong Yu; Hongjun Wang; Chuanjie Cheng; Zhuang Ruan; Tongcui Guo; Liangjie Zhang; Muwei Cheng (Arabian Journal of Geosciences, 2019)

The concurrent effects of the South Asian monsoon and the plateau monsoon over the Tibetan Plateau on summer rainfall in the Tarim Basin of China - Yong Zhao; Xiaojing Yu; Junqiang Yao; Xinning Dong; Hongjun Li (International Journal of Climatology, 2019)
Based on the observed rainfall data at 34 stations over the Tarim Basin (TB) and the National Centers for Environmental Prediction/National Center for Atmospheric Research reanalysis data during 1961–2012, the concurrent effects of the plateau monsoon (PM) over the Tibetan Plateau and the South Asian monsoon (SAM) on summer rainfall over the TB are investigated. Mid‐upper tropospheric temperature (MUTT) plays an important role in linking the PM and the SAM with summer rainfall over the TB. The concurrent influential mechanisms of the PM and the SAM on summer rainfall over the TB can be summarized as follows. The strengthened (weakened) PM and the weakened (strengthened) SAM cause mid‐upper tropospheric cooling (warming), which tends to result in the migration of the subtropical westerly jet further southward (northward). Then an anomalous southerly (northerly) flow prevails over the TB, and more (less) water vapour is transported into the TB by a two‐step process. All above contribute significantly to an increase (decrease) in the occurrence of summer rainfall over the TB. In addition, we also discuss the relative contribution of the PM and the SAM to summer rainfall over the TB. Partial correlations show that the PM and the SAM can both individually influence summer rainfall over the TB. The PM has a direct effect on summer rainfall over the TB, for its considerable relations not only with MUTT but also with atmospheric circulation. Whereas the SAM has an indirect effect for its only influence on MUTT, which then give rise to an anomalous circulation related to summer rainfall over the TB.

Projected changes in the annual cycle of precipitation over central Asia by CMIP5 models - Xiaojing Yu; Yong Zhao; Xiaojiao Ma; Junqiang Yao; Hongjun Li (International Journal of Climatology, 2018)
Future changes in the annual cycle of the precipitation in central Asia (CA) were estimated based on the historical and representative concentration pathway 8.5 (RCP8.5) experiments from 25 models of the Coupled Model Intercomparison Project phase 5. Compared with the Global Precipitation Climatology Project observations, the historical (1979–1999) experiments showed that most models can capture the migration of rainfall centres, but remarkable discrepancies exist in the location and intensity of rainfall centres between simulations and observations. Considering the skill scores of precipitation and pattern correlations of circulations, which are closely related to the precipitation for each month, for the 25 models, the four best models (e.g., CanESM2, CMCC‐CMS, MIROC5 and MPI‐ESM‐LR) with relatively good performance were selected. The four models' ensemble mean indicated that the migration and location of the precipitation centres were better reproduced, except the intensity of the centres was overestimated, compared with the result that only took the precipitation into consideration. Based on the four best models' ensemble mean under RCP8.5 scenarios, precipitation was projected to increase dramatically over most of the CA region in the boreal cold seasons (November, December, January, February, March and April) and May, with the maximum in December at the end of 21st century (2079–2099), and several positive centres were located in the Pamirs Plateau, the Tianshan Mountains and the northern Himalayas. The precipitation changes were weak in the boreal warm seasons (June, July, August, September and October), with a dry centre located in the Pamirs Plateau and a wet centre in the northern Himalayas. These projected changes can be directly attributed to the overlay of anomalous moisture convergence and evaporation, and other possible mechanisms of dynamic and thermodynamic factors need to be further elucidated.

Geochemistry of pyrite and chalcopyrite from an active black smoker in 49.6°E Southwest Indian Ridge - Bo Yuan; Yaomin Yang; Hongjun Yu; Yuexia Zhao; Qingfeng Ding; Jichao Yang; Xin Tang (Marine Geophysical Research, 2018)

A New Approach of Rpf Addition to Explore Bacterial Consortium for Enhanced Phenol Degradation Under High Salinity Conditions - Ziqiao Li; Yunge Zhang; Yuyang Wang; Rongwu Mei; Yu Zhang; Muhammad Zaffar Hashmi; Hongjun Lin; Xiaomei Su (Current Microbiology, 2018)

Oil mixing behavior after an oil spill: identification conflicts of different fingerprints - Shijie He; Hongjun Yu; Yongming Luo; Chuanyuan Wang; Xueshuang Li; Zhongping Li (Environmental Science and Pollution Research, 2018)

The impact of modern plant breeding on dominant Chinese wheat cultivars (Triticum aestivum L.) revealed by SSR and functional markers - Lingzhi Meng; Chao Xiang; Hongwei Liu; Li Yang; Chunyan Mai; Liqiang Yu; Yunliang Wei; Hongjie Li; Hongjun Zhang; Yang Zhou (Genetic Resources and Crop Evolution, 2018)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)

Molecular variation and expansion of a rice black-streaked dwarf virus population based on analysis of segment 1 in Jining, China - Yu Zhou; Qingchang Meng; Yanping Chen; Jirong Wu; Zhuanfang Hao; Zhenhua Wang; Degui Zhang; Mingshun Li; Hongjun Yong; Shihuang Zhang; Xinhai Li; Jianfeng Weng (Archives of Virology, 2016)

Numerical Model-Based Artificial Neural Network Model and Its Application for Quantifying Impact Factors of Urban Air Quality - Jianjun He; Ye Yu; Yaochen Xie; Hongjun Mao; Lin Wu; Na Liu; Suping Zhao (Water, Air, & Soil Pollution, 2016)

Distinct Hippocampal Expression Profiles of lncRNAs in Rats Exhibiting a PTSD-like Syndrome - Liu Qingzhen; Ma Jiehua; Yu Zhiyang; Liu Hongjun; Chen Chunlong; Li Weiyan (Molecular Neurobiology, 2016)

Efficacy and safety of quetiapine extended release monotherapy in bipolar depression: a multi-center, randomized, double-blind, placebo-controlled trial - Huafang Li; Niufan Gu; Hongyan Zhang; Gang Wang; Qingrong Tan; Fude Yang; Yuping Ning; Honggeng Zhang; Zheng Lu; Xiufeng Xu; Jianguo Shi; Chengge Gao; et al. (Psychopharmacology, 2016)

Evaluation of diagnostic ratios of medium and serious weathered oils from five different oil sources - Shijie He; Chuanyuan Wang; Yantai Li; Hongjun Yu; Bin Han (Acta Oceanologica Sinica, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

Paleoenvironmental changes during the late Quaternary as inferred from foraminifera assemblages in the Laizhou Bay - Jing Yao; Hongjun Yu; Xingyong Xu; Liang Yi; Guangquan Chen; Qiao Su (Acta Oceanologica Sinica, 2014)

Characterization of 10 polymorphic microsatellite markers for Mediterranean blue mussel Mytilus galloprovincialis by EST database mining and cross-species amplification - HONGJUN LI; YU LIANG; LIJUN SUI; XIANGGANG GAO; CHONGBO HE (Journal of Genetics, 2013)

Distribution of phthalate esters in topsoil: a case study in the Yellow River Delta, China - Yang Hongjun; Xie Wenjun; Liu Qing; Liu Jingtao; Yu Hongwen; Lu Zhaohua (Environmental Monitoring and Assessment, 2013)

Intracellular Cu/Zn superoxide dismutase (Cu/Zn-SOD) from hard clam Meretrix meretrix: its cDNA cloning, mRNA expression and enzyme activity - Xianggang Gao; Chongbo He; Hong Liu; Hongjun Li; Dan Zhu; Shengli Cai; Ying Xia; Ying Wang; Zhe Yu (Molecular Biology Reports, 2012)

Whole genome sequencing and biological characterization of Duck/JS/10, a new lentogenic class I Newcastle disease virus - Chunchun Meng; Xvsheng Qiu; Shiqiang Jin; Shengqing Yu; Hongjun Chen; Chan Ding (Archives of Virology, 2012)

Enzymatic and biological characteristics of enolase in Brucella abortus A19 - Xiangan Han; Chan Ding; Hongjun Chen; Qinghai Hu; Shengqing Yu (Molecular Biology Reports, 2012)

Reconstructions of annual summer precipitation and temperature in north-central China since 1470 AD based on drought/flood index and tree-ring records - Liang Yi; Hongjun Yu; Junyi Ge; Zhongping Lai; Xingyong Xu; Li Qin; Shuzhen Peng (Climatic Change, 2012)

The color reflectance of marine-terrigenous deposits in LZ908 borehole in south coastal plain of the Laizhou Bay - Na Zhao; Xingyong Xu; Hongjun Yu; Jing Yao; Qiao Su; Shuzhen Peng (Acta Oceanologica Sinica, 2011)

Construction of mini-Tn4001 transposon vector for Mycoplasma gallisepticum - HongJun Chen; ChunMei Zhao; XieYue Shen; DanQing Chen; ShengQing Yu; Chan Ding (Science China Life Sciences, 2010)